Synthesis of potential anti-tumoral ring a substituted tieno[3,2-c]carbazoles from diarylamines - Ferreira, Isabel C.F.R. (2002)
Thienocarbazoles bearing electron donating or withdrawing groups in ring a, were prepared by intramolecular oxidative cyclization of diarylamines using stoichiometric or catalytic Pd(OAc)2 amounts, in fair to moderate yields. ln the latter case Cu(OAch was added to reoxidize Pd(O) forrned. The diarylamine precursors were prepared by palladium-catalysed amination.